Distributed robust composite-rotating consensus of second-order multi-agent systems - Weizheng Huang; Wenfeng Zheng; Lipo Mo (International Journal of Distributed Sensor Networks)
In this article, the distributed H ∞ composite-rotating consensus problem is concerned for a class of second-order multi-agent systems. First, based on local state feedback and communication feedback, a distributed control algorithm is proposed. Then, sufficient conditions are derived in order to make all agents reach a composite-rotating consensus with the desired H ∞ performance. Finally, the simulations are given to show the effectiveness of the theoretical results.